A series of five patients with oxyntic gland adenoma: deciphering the clinical and histological features of these rare gastric polyps - Nagaputra, Jerry C. (2022)
Oxyntic gland adenomas are rare lesions of the stomach, composed of oxyntic-type glands. A variety of nomenclatures have been used to designate it, including adenocarcinoma of fundic gland type and oxyntic mucosa pseudo-polyp. We report a series of five cases that demonstrate a spectrum of clinical and morphological variations in oxyntic gland adenomas. Although all cases showed irregular, dilated oxyntic glands lined by predominantly chief cells with scattered parietal cells, one case showed at least moderate cytological atypia and another showed submucosal invasion. Despite these worrying features, all patients had no evidence of recurrence following successful endoscopic resections.